Kemandirian Ekonomi Etnik Nias Sebagai Strategi Kebertahanan Menghadapi Eksklusi Sosial (Studi Kasus: Tukang Pangkas dan Tukang Jahit Etnik Nias Kecamatan Tarutung) - Donny H. Zalukhu; Elvri T. Simbolon; Wensdy Sitindaon; Roida Lumbantobing; Harisan B. Firmando (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the Economic Independence of the Nias Ethnic Group as a survival strategy in the face of social exclusion in Tarutung District, North Tapanuli Regency. The research method used was qualitative research. Data collection using techniques, observation, interviews and documentation. From the results of the study obtained. The economic independence of the Nias ethnic group can be seen from the existence of barbershops and tailors that have developed in Tarutung District. Social exclusion occurs among the Nias ethnic group which results in the Nias ethnic group preferring to create their own businesses. The economic adaptation strategy of the Nias ethnic group in Tarutung District, North Tapanuli Regency, that the economic adaptation strategy carried out by the Nias Ethnic Group is generally by utilizing social networks by utilizing social networks of family, friends, and communities. The Nias ethnic group who migrated to Tarutung, some of them have family or relatives who have migrated to Tarutung. Through the use of this network, the Nias ethnic group is able and easy to get information opportunities regarding job opportunities and business opportunities. Managing their own business is adjusted to their interests or skills, this business is limited in scale and managed by one individual. The Nias ethnic group establishes their own business because they have capital, either from capital collected by themselves or capital assistance from their families. adapting to existing jobs and in accordance with their respective skills. The development of the barbershop or sewing business of the Nias ethnic group in Tarutung greatly influences the development of the economic progress of the Nias ethnic group in Tarutung.